PEMIKIRAN ANREGURUTTA HAJI DAUD ISMAIL TENTANG AKHLAK MANUSIA - Jannah, Sitti Riadil (Universitas Islam Negeri Alauddin Makassar, 2022)
Anregurutta Haji Daud Ismail's thoughts about human morality can be understood that morality as a value system that characterizes human life is one of the vessels in building a transcendental relationship between al-Khalik and His creatures. In this context, it can be seen that there are two moral dimensions in the thinking of this Bugis-born charismatic cleric, namely the esoteric dimension on the one hand and the exoteric dimension on the other. Humans in their lives are very likely to commit various sins which basically they wrong themselves. Therefore, humans must continue to improve their morals by making istighfar or repenting to the God. In the thought of Anregurutta Haji Daud Ismail, human morals are divided into morals towards Allah SWT. and morals to fellow human beings with various forms of elaboration which are described in detail in his commentary, namely al-Munir.